Violence-related distress and lung function in two longitudinal studies of youth. Issue 5 (12th May 2022) - Gaietto, Kristina; Han, Yueh-Ying; Forno, Erick; Bacharier, Leonard B.; Phipatanakul, Wanda; Guilbert, Theresa W.; Cabana, Michael D.; Ross, Kristie; Blatter, Joshua; Acosta-Pérez, Edna; Miller, Gregory E.; de la Hoz, Rafael E.; et al.
Background: Exposure to violence has been associated with lower lung function in cross-sectional studies. Methods: We examined whether increasing violence-related distress over time is associated with worse lung function and worse asthma control or quality of life in a secondary analysis of a 48-week randomised clinical trial in 98 youth with asthma (aged 9–16 years) treated with low-dose inhaled corticosteroids (Vitamin D Kids Asthma Study (VDKA)). We then replicated our findings for lung function in a prospective study of 232 Puerto Rican youth followed for an average of 5.4 years. Violence-related distress was assessed using the Checklist of Children's Distress Symptoms (CCDS) scale. Our outcomes of interest were percent predicted lung function measures and (in VDKA only) asthma control (assessed using the Asthma Control Test) and asthma-related quality of life (assessed using the Pediatric Asthma Quality of Life Questionnaire (PAQLQ)). Results: In a multivariable analysis in VDKA, each 1-point increment in CCDS score was associated with decrements of 3.27% in forced expiratory volume in 1 s (FEV1 ) % pred (95% CI −6.44– −0.22%; p=0.04), 2.65% in forced vital capacity (FVC) % pred (95% CI −4.86– −0.45%; p=0.02) and 0.30 points in the overall PAQLQ score (95% CI −0.50– −0.10 points; p<0.01). Similar findings for FEV1 and FVC were obtained in the prospective study of Puerto Rican youth. Conclusions: Our findings suggest that violence-related distress may worsen lung function and quality of life in youth with asthma (even those treated with low-dose inhaled corticosteroids), and further support policies to reduce exposure to violence among children in the USA and Puerto Rico. Increasing violence-related distress over time was associated with worse lung function and worse asthma-related quality of life in youth with asthma despite treatment with low-dose inhaled corticosteroids https://bit.ly/3zL1vXM